Developmental Trajectories of Adolescents' Math Motivation: The Role of Mindset and Perceptions of Informal STEM Learning Site Inclusivity. - Ozturk, Emine; Zhao, Mengya; Hoffman, Adam J.; Joy, Angelina; Marlow, Christina S.; Law, Fidelia; Deutsch, Ashley R.; Mathews, Channing J.; McGuire, Luke; Balkwill, Frances; Burns, Karen; Butler, Laurence; et al. (Journal of Youth & Adolescence, 2024)
Motivation is a key factor in engagement, achievement, and career choices in science, technology, engineering, and mathematics (STEM). While existing research has focused on student motivation toward math in formal school programs, new work is needed that focuses on motivation for those involved in informal STEM programs. Specifically, the role of math mindset and perceived inclusivity of informal STEM sites (to those of varying gender and ethnic backgrounds) on longitudinal trajectories of adolescents' math motivation has not been explored. This study investigates longitudinal changes in math expectancy, interest, and utility values and the effects of math fixed mindset, math growth mindset, and perceptions of the inclusivity of informal STEM learning sites on these changes for adolescents participating in STEM programs at these informal sites in the United Kingdom and the United States (n = 249, M = 15.2, SD = 1.59). Three latent growth curve models were tested. The data suggest that math expectancy, interest, and utility values declined over three years. Growth mindset positively predicted changes in utility, while fixed mindset negatively predicted changes in utility. Inclusivity positively influenced the initial levels of utility. Girls reported lower initial expectancy than boys. Age influenced both the initial levels and rate of change for expectancy. Older adolescents had lower levels of expectancy compared to their younger counterparts; however, they had a less steep decline in expectancy over three years. These findings suggest that designing inclusive learning environments and promoting growth mindset may encourage math motivation.